Penerapan Jaringan Syaraf Tiruan Backpropagation Dalam Memprediksi Jumlah Pertumbuhan Kendaraan Di Provinsi Sumatera Utara - Bagus Supranda; S Solikhun; Zulia Almaida Siregar (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
Motorized vehicles are part of the need for transportation of vehicles that are derivatives due to economic, social, and other activities. The growth of vehicles is not proportional to the population in the province of North Sumatra. This causes various negative impacts, one of which is an increase in traffic congestion, air pollution from motorized vehicles which causes an increase in greenhouse gas emissions. Based on this problem, it is necessary to predict the number of vehicles in North Sumatra Province using the backpropagation algorithm artificial neural network. The results of trials carried out with MATLAB R2011b software, the best architectural model is the 2-2-1 model with an accuracy rate of 94% with MSE number 0.000208514, epoch value 789. It can be concluded that the Backpropagation method can be used as one of the predictive methods that make it easier to find predictions. Whatever.